Aspectos da estrutura, funcionamento e manejo da reserva particular do patrimônio natural "Ecoparque de Una": região cacaueira do Sul da Bahia, Brasil - Schiavetti, Alexandre (2002)
The cocoa production region of southern Bahia harbors the largest fragments of Atlantic Forest in the State of Bahia, possessing a high frequency of endemics and species richness, and being presently considered a priority area for biodiversity conservation. Nevertheless, the process of implementing Conservation Units in the region is not keeping up with the rate of change in local land use. Among the strategies of non-governmental organizations to help in the conservation of the Una Biological Reserve (the largest forest fragment in the cocoa production region) is the creation of Private Nature Reserves. In the present work, the process of implementation of the Ecoparque do Una Private Nature Reserve was assessed. The Ecoparque do Una is a 383 ha area contiguous to the Una Biological Reserve (UBR), and is intended to be a model for sustainable development and natural resource utilization. The analysis of the social and economic relations between the Ecoparque and its neighboring properties indicated that both areas lack economic integration. However, employees at the Ecoparque are all native to the region, a situation that contributes for the Ecoparque to be more easily accepted by the local community. The number of visitors to the area is increasing monthly from 1998 to present, but the public is constituted typically by people coming from other regions. This limits the process of comprehension, by people from the cocoa production region, of the importance of the Ecoparque for conservation of natural resources. The cost of the entry ticket to the Ecoparque was pointed by tourism operators as the greatest barrier for marketing the Ecoparque as a product, restricting the aggregate value of tourism in the region. In spite not being yet an economically sustainable touristic product, because its expenditures are higher than the direct incomes from public visitation, this model of development is in process of becoming sustainable. All the environmental factors considered, the Ecoparque is meeting the requisites of a sustainable enterprise with social responsibility, environmental conservation and economic development.